Test Tubes for Global Intellectual Property Issues Small Market Economies - Frankel, Susy (Cambridge Intellectual Property and Information Law, 2015)
Small market economies provide a valuable insight into how a country might balance competing interests in global intellectual property. As developed countries that are also net-importers of intellectual property, small market economies have similar concerns to some developing countries. This duality of developed and developing country interests has resulted in some innovative ways of calibrating laws so that they both support national economic and social needs and honour international commitments. In this book, Susy Frankel uses examples from the small market economies of Singapore, New Zealand and Israel to address global intellectual property issues. Those issues include approaching treaty interpretation to both assist in implementation of obligations and utilisation of flexibilities, and effective dispute resolution; the links between trade and innovation; when and how patent and copyright law can be flexible; the importance of trade marks to small businesses; parallel importing; and the protection of traditional knowledge